Bone metastasis from malignant phyllodes of the breast - Dau, Daniel Oktavianus; Sudarsa, I. Wayan (International Journal of Research in Medical Sciences, 2019)
Cystosarcoma phyllodes was described first in 1838 and originally was considered to be a benign tumor. It was not until 1931 that metastasis from a cystosarcoma phyllodes was reported. The incidence of cystosarcoma phyllodes is estimated to be 0.3% to 0.9% of all breast tumors. Sites most commonly affected by metastases are the lungs and bones. We present a case report 29-year old female patient presented with a voluminous breast mass at both of them which was completely resected. The right side presented of malignant phyllodes and the left side is borderline phyllodes. Six months later, both of her legs became paralyzed and accompanied by swelling over her right upper arm. Biopsy was performed, and the diagnosis was metastatic malignant phyllodes tumor. Histologic review of the breast tumor revealed stromal overgrowth.